PENERAPAN MEDIA MONOPOLI TERHADAP HASIL BAHASA INDONESIA KELAS IV SD NEGERI 2 LUBUK NGIN - Cicilia Septriani; Satinem Satinem; Andriana Sofiarini (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the completeness of the results of learning Indonesian on the application of monopoly media for class IV SD Negeri 2 Lubuk Ngin. The type of research is quasi-experimental. Population of all grade IV SD Negeri 2 Lubuk Ngin. A total of 34 students. The sample is Class IV.A students, totaling 16 students. Data collection through essay tests. The collected data were analyzed using the t-test at a significant level = 0.05. Obtained tcount (6.87) > ttable (1.76). So it can be concluded that the learning outcomes of class IV students at SD Negeri 2 Lubuk Ngin are complete after participating in learning Indonesian with monopoly media. Keywords: Media monopoly, Indonesian language learning outcomes